Indications to Hospital Admission and Isolation of Children With Possible or Defined Tuberculosis: Systematic Review and Proposed Recommendations for Pediatric Patients Leaving in Developed Countries. Issue 50 (December 2015) - Vecchio, Andrea Lo; Bocchino, Marialuisa; Lancella, Laura; Gabiano, Clara; Garazzino, Silvia; Scotto, Riccardo; Raffaldi, Irene; Assante, Luca Rosario; Villani, Alberto; Esposito, Susanna; Guarino, Alfredo
Abstract : Abstract: Tuberculosis (TB) is a re-emerging health problem in developed countries. This paper is part of large guidelines on the global management of TB in children, by a group of scientific societies. It describes the indications to hospitalization of children with suspected or diagnosed TB, the isolation measures, hospital discharge, and re-admission into the community. Using the Consensus Conference method, relevant publications in English were identified by means of a systematic review of MEDLINE and the Cochrane Database of Systematic Reviews from their inception until 31 December 2014. Available data on indications to hospitalization were mainly indirect and largely derived from observational studies. They include: (1) host-related risk factors, the main being age <12 months, immune deficiencies, and malnutrition; (2) TB-related clinical conditions that resemble those of pneumonia but also include drug-resistance; and (3) social and logistic conditions. The latter are based on opinion and depend on local conditions. Analysis of the literature showed that patients hospitalized with suspected pulmonary TB should be put in precautionary respiratory isolation regardless of their age while they await diagnosis. The general conditions for re-admission into the community are at least 14 days of effective treatment and negative microscopic tests of 3 consecutive samples in previously microscopically positive patients. This is the first paper that provides indications to hospitalization of children with TB. Most recommendations are generally applicable in all developed countries. Some might need an adaptation to local setting, epidemiological, parameters, and availability of specific health-care facilities.